Stem Cells, Self-Renewal, and Lineage Commitment in the Endocrine System - Mariniello, Katia; Ruiz-Babot, Gerard; McGaugh, Emily C.; Nicholson, James G.; Gualtieri, Angelica; Gaston-Massuet, Carles; Nostro, Maria Cristina; Guasti, Leonardo (Frontiers in Endocrinology, 2019)
The endocrine system coordinates a wide array of body functions mainly through secretion of hormones and their actions on target tissues. Over the last decades, a collective effort between developmental biologists, geneticists, and stem cell biologists has generated a wealth of knowledge related to the contribution of stem/progenitor cells to both organogenesis and self-renewal of endocrine organs. This review provides an up-to-date and comprehensive overview of the role of tissue stem cells in the development and self-renewal of endocrine organs. Pathways governing crucial steps in both development and stemness maintenance, and that are known to be frequently altered in a wide array of endocrine disorders, including cancer, are also described. Crucially, this plethora of information is being channeled into the development of potential new cell-based treatment modalities for endocrine-related illnesses, some of which have made it through clinical trials.